Mathematical Modelling and Techno-economic Evaluation of Hybrid Photovoltaic-thermal Forced Convection Solar Drying of Indian Jujube (Zizyphus mauritiana) - Poonia, Surendra; Singh, A. K.; Jain, Dilip (Journal of Agricultural Engineering, 2019)
Two identical units of a hybrid photovoltaic-thermal (PV/T) solar dryer designed and constructed at ICAR-Central Arid Zone Research Institute, Jodhpur, were used to dry Indian jujube (Zizyphus mauritiana) fruit, one operated under natural and the other under forced convection modes. The fruits were dried to safe moisture content (24 %) in a period of 192 h in forced convection mode, and in 240 h in natural convection mode with drying load of 18 kg. There was a significant difference in performance of the dryer under forced and natural convection mode. The average thermal efficiency of solar energy utilization under forced convection mode was higher (16.7 %) than that of natural convection solar dryer (15.6 %). Logarithmic drying model was suitable for describing the thin layer drying behaviour of the fruit. Effective moisture diffusivity of forced convection dryer was 3.34 Ã— 10-7 m2.s-1. Economic evaluation of the solar dryer indicated high value of IRR (54.5 %), and low value of payback period (2.26 years), suggesting the dryer to be cost efficient.